Використання фільтрату барди при приготуванні зернових замісів - Шиян, Петро Леонідович; Мудрак, Тетяна Омелянівна; Боярчук, Ярослав Андрійович; Сосницький, Віталій Володимирович (My University, 2015)
Проведено дослідження спиртового зброджування крохмалевмісної сировини із заміною технологічної води фільтратом барди на стадії приготування замісу. Встановлено, що використання фільтрату барди впливає на синтез летких органічних домішок спирту. Визначено оптимальну кратність використання фільтрату барди на стадії приготування замісу. In a market economy to the domestic alcohol industry faces challenges, first and foremost, is to reduce production costs through the development and implementation of principally new innovative technologies that provide increased specific output of commodity products while maximizing utilization of waste. Analysis alcoholic fermentation of starch mash the replacement process water filtrate bards at the stage batch cooking. It was established that the use of leachate bards positively affects the activity of yeast cells, reducing the synthesis of volatile organic impurities and acids. Defined maximum number of replacement water use and multiplicity filtrate bards at the stage of preparation of mixing depending on the dry matter content in the must
Keywords: кафедра біотехнології продуктів бродіння і виноробства; зброджування; сусло; фільтрат барди; леткі органічні домішки спирту; кратність використання фільтрату барди; of the filtrate bards; fermentation mash filtrate bards; volatile organic impurities of alcohol; use of the multiplicit